Lyophilized aqueous extracts of Mori Fructus and Mori Ramulus protect Mesenchymal stem cells from •OH-treated damage: bioassay and antioxidant mechanism - Qian Jiang; Xican Li; Yage Tian; Qiaoqi Lin; Hong Xie; Wenbiao Lu; Yuguang Chi; Dongfeng Chen (BMC, 2017)
Abstract Background Mori Fructus and Mori Ramulus are two traditional Chinese herbal medicines from mulberries. The present work explores their beneficial effects on •OH-treated mesenchymal stem cells (MSCs) and discusses possible mechanisms. Methods Lyophilized aqueous extracts of Mori Fructus (LAMF) and Mori Ramulus (LAMR) were prepared and analyzed using HPLC. LAMF and LAMR (along with morin) were further investigated for their effects on •OH-treated MSCs using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl (MTT) assay. The direct antioxidation mechanisms were studied using 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (PTIO•)-scavenging, 2,2'-azino-bis (3-ethylbenzo-thiazoline-6-sulfonic acid (ABTS+•)-scavenging and 1,1-diphenyl-2-picryl-hydrazl (DPPH•)-scavenging, as well as Cu2+-reducing and Fe3+-reducing antioxidant power. Finally, the indirect antioxidant mechanism was investigated based on the UV-vis spectra of Fe2+-chelation. Results In each LAMF and LAMR, seven phytophenols were successfully measured by HPLC, including five flavonoids (morin, rutin, astragalin, isoquercitrin and luteolin) and two non-flavonoids (chlorogenic acid and maclurin). MTT assays revealed that LAMF, LAMR and morin could effectively increase the survival of •OH-treated MSCs at 10-100 μg/mL, and could effectively scavenge PTIO• (IC 50 6609.7 ± 756.6, 4286.9 ± 84.9 and 103.4 ± 0.9 μg/mL, respectively), DPPH• (IC 50 208.7 ± 3.0, 97.3 ± 3.1 and 8.2 ± 0.7 μg/mL, respectively) and ABTS+• (IC 50 73.5 ± 5.8, 34.4 ± 0.1 and 4.2 ± 0.2 μg/mL, respectively), and reduce Cu2+ (IC 50 212.5 ± 7.0, 123.2 ± 0.9 and 14.1 ± 0.04 μg/mL, respectively) & Fe3+ (IC 50 277.0 ± 3.1, 191.9 ± 5.2 and 5.0 ± 0.2 μg/mL, respectively). In the Fe2+-chelating assay, the five flavonoids produced much stronger shoulder-peaks than the two non-flavonoids within 420-850 nm. Conclusion Mori Fructus and Mori Ramulus, can protect MSCs from •OH-induced damage. Such beneficial effects can mainly be attributed to the antioxidant action of phytophenols, which occurs via direct (ROS-scavenging) and indirect mechanism (Fe2+-chelating). The ROS-scavenging mechanism, however, include at least a H+-transfer and an electron-transfer (ET), and possibly includes a hydrogen-atom-transfer (HAT). In the Fe2+-chelating, flavonoids are more effective than non-flavonoids. This can be attributed to several adjacent planar chelating-sites between the 3-OH and 4-C = O, between the 4-C = O and 5-OH, or between the 3'-OH and 4'-OH in flavonoids. Such multiple-Fe2+-chelating reactions cause overlap in the UV-vis absorptions to deepen the complex color, enhance the peak strength, and form shoulder-peaks. By comparison, two non-flavonoids with catechol moiety produce only a weak single peak.